Students with disabilities as ideal graduates: universities' obligations to support extracurricular involvement - Brooke Szucs; Paul Harpur (Journal of Teaching and Learning for Graduate Employability, 2023)
Extracurricular activities (ECAs) and their impact on student employability has become a focus of the higher education sector, with a recent emphasis on experiences such as global exchange and skill acquisition that prepares graduates for the workforce. Despite the initiatives and effort put into supporting the general student population, students with disabilities are underrepresented in these opportunities. This causes such students to have less access to employability opportunities that set them apart from their peers and leads to a distinct disadvantage when seeking to enter the workforce. The literature suggests that there are various benefits of participating in extracurricular activities for university students, including some literature about students with disabilities. However, there is a distinct lack of focus on how the scarcity of support for participation in these programs fails to address equality and discrimination legal obligations, as well as the failure of disability specific initiatives to include these activities as essential to their core mission. This paper aims to examine how Australian University strategic plans addressing disability inclusion and supports for students with disabilities extend to the extracurricular space, and what more can be done to include these students in all aspects of campus life. Through a search and policy analysis of University Strategic Plans, Disability Action Plans, and scholarships for students with disabilities to participate in extracurricular activities, it was revealed that this issue is not being sufficiently addressed through university strategic responses to disability inclusion. This paper provides practitioners and universities with recommendations to improve their compliance with antidiscrimination measures and address this deficit to improve student outcomes.